Digital Anti-Cyberbullying Campaign through a Student Collaboration Project - Nur Elfi Husda; Michael Jibrael Rorong; Muhammat Rasid Ridho; Nurhabsyina; Faine Fabiola; Khairuddin (Jurnal Pengabdian Sains dan Humaniora, 2026)
The rapid growth of social media has intensified adolescents’ digital interactions while increasing the risk of cyberbullying, which negatively affects students’ psychological well-being. Low digital literacy and limited understanding of online ethics are key factors contributing to adolescents’ vulnerability to online harassment. This community service program aimed to enhance students’ awareness and understanding of ethical and responsible social media use through a collaborative digital campaign project. The program employed a Participatory Action Research (PAR) approach consisting of observation, problem formulation, intervention, and evaluation. The participants were students of SMA Negeri 28 Batam from various grade levels. The intervention was conducted through poster design and digital content creation competitions focusing on cyberbullying prevention. The results indicate increased student engagement, improved understanding of online ethics, and greater awareness of the dangers of hoaxes and cyberbullying. In addition, the program contributed to the development of students’ soft skills, including teamwork, creativity, and communication. This collaborative project demonstrates its potential as a participatory and sustainable digital literacy education model for cyberbullying prevention among students.